Inverse Problem for Determination of An Unknown Coefficient in the Time Fractional Diffusion Equation - Demir, Ali; Bayrak, Mine Aylin (Communications in Mathematics and Applications, 2018)
The fundamental concern of this article is to apply the residual power series method (RPSM) effectively to determine of the unknown coefficient in the time fractional diffusion equation in the Caputo sense with over measured data. First, the fractional power series solution of inverse problem of unknown coefficient is obtained by residual power series method. Finally, efficiency and accuracy of the present method is illustrated by numerical examples.